The psychiatric management of prisoners on hunger strike: developing a management algorithm using the Delphi technique. Issue 1 (20th February 2019) - Gulati, Gautam; Kelly, Brendan D.; O'Neill, Conor; O'Connell, Paul; Linehan, Sally; Spain, Eimear; Meagher, David; Dunne, Colum P.
Abstract : Purpose: The assessment and management of prisoners on hunger strikes in a custodial setting is complex. There is limited clinical guidance available for psychiatrists to draw upon in such cases. The purpose of this paper is to develop a management algorithm through expert elicitation to inform the psychiatric care of prisoners on a hunger strike. Design/methodology/approach: A Delphi method was used to elicit views from Irish forensic psychiatrists, a legal expert and an expert in ethics using a structured questionnaire. Themes were extracted from the results of the questionnaire to propose a management algorithm. A consensus was reached on management considerations. Findings: Five consultant forensic psychiatrists, a legal expert and an expert on psychiatric ethics ( n =7) consented to participation, with a subsequent response rate of 71.4 per cent. Consensus was achieved on a proposed management algorithm. Assessment for mental disorder, capacity to refuse food and motivation for food refusal are seen as key psychiatric tasks. The need to work closely with the prison general practitioner and the value of multidisciplinary working and legal advice are described. Relevant aspects of law included mental health, criminal law (insanity) and capacity legislation. Originality/value: This study outlines a management algorithm for the psychiatric assessment and management of prisoners on a hunger strike, a subject about which there is limited guidance to date. Although written from an Irish perspective, this study outlines key considerations for psychiatrists in keeping with international guidance and therefore may be generalisable to other jurisdictions.